Copyright and innovation: Fit for digitization? - Christian Handke; Yann Girard; Anselm Mattes (DIW Economic Bulletin, 2015)
It is contentious to what extent the existing copyright system contributes to the positive development of the regulated sectors of society. The present report shows that substantially more musical works and movies have been released in recent years than before the diffusion of digital copying technology. At the same time, the average quality of these works has been stable according to user assessments. Countries with stronger copyright protection do not exhibit greater supply of new works. Accordingly, the relatively strict copyright protection in some countries does not seem to promote the supply of new creative works. The present report also considers whether user-generated content (UGC) complements or substitutes professional content. An increasing supply of valuable UGC is not reflected in official economic statistics. In all probability, copyright protection promotes user-generated content less than professional content. As a result, substituting professional content with "amateur material" could reduce the socially desirable strength of copyright protection. However, we find that almost half of all works available on YouTube are professional content. Professional works are watched and recommended more frequently than the average. In addition, a large proportion of UGC on YouTube draws on professional works. There is little evidence that professional content would be widely replaced. It follows that UGC could also be supported by an efficient copyright system, which strengthens the supply of professional content without excessively limiting its further use as input for UGC.
Keywords: O31; O34; D23; Z11; 330; innovation; copyright; digitization; user-generated content; creative industries